Mind-body health in the school environment - Bray, Melissa A; Maykel, Cheryl (International Journal of School and Educational Psychology, 2016)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-180-143-210-553 tex.type: [object Object]
Keywords: dept.csp

Thinking in new ways and in new times about reading - Leu, Donald J; Maykel, Cheryl (Literacy Research and Instruction, 2016)
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-033-594-976-852 tex.type: [object Object]
Keywords: dept.csp

Love thy neighbor: A guide for implementing safe school initiatives for LGBTQ students in nonaffirming religious communities - Ginicola, Misty M; Smith, Cheri; Rhoades, Elizabeth (Journal of LGBT Issues in Counseling, 2016)
Although setting up a safe school is an important task for a school counselor, his or her efforts may be resisted when attempting to develop a safe school initiative in a religious community; for example, one conservative-based website gives parents explicit instructions on how to fight a school's safe schools initiatives. This article provides a review of the issues involved and a specific framework for school counselors who wish to set up a Safe Schools Initiative in the context of a resistant atmosphere, using a social justice framework. © 2016 Taylor & Francis Group, LLC.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/101-808-473-793-033 tex.type: [object Object]
Keywords: LGBTQ; dept.csp; religious conflict; safe schools; school counseling; social justice

Psychologically based therapies to improve lung functioning in students with asthma. - Maykel, Cheryl; Bray, Melissa A; Gelbar, Nicholas W; Caterino, Linda C; Avitia, Maria J; Sassu, Kari; Root, Melissa M (International journal of school and educational psychology, 2016)
Asthma is a common, chronic respiratory disease that can be costly to both society and the individual. In addition to increased absenteeism, children with asthma may also be at a greater risk for developing comorbid anxiety and depression. Various complementary psychological treatments have been effective at reducing both asthmatic symptoms and psychological distress. Although the research in the area of mind-body treatments as it pertains specifically to persons with asthma is still developing, this article will describe several promising alternative treatment methods, many of which have already been, or could be easily be applied for use in a school setting. © 2016, © 2016 International School Psychology Association.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-833-211-583-544 tex.type: [object Object]
Keywords: art therapy; asthma; biofeedback; dept.csp; hypnosis; mind-body; mindfulness; music therapy; relaxation and guided imagery; school-based interventions; written emotional expression; yoga

Students with cancer: presenting issues and effective solutions. - Root, Melissa M; Bray, Melissa A; Maykel, Cheryl; Cross, Karen; Shankar, Nilani L; Theodore, Lea A (International Journal of School and Educational Psychology, 2016)
Practitioners working with children diagnosed with cancer in the school environment must consider several facets in order to effectively work with the child and family. The remission rate for children with cancer is relatively high, so one must consider whether the child is anticipating treatment, actively in treatment, or posttreatment when one thinks about the potential stressors and cognitive impacts of cancer on the child's education. This article focuses on facts associated with childhood cancer that are relevant to school-based practitioners, common stressors for children and adolescents with a personal cancer diagnosis in their lives, research-based interventions, and accommodations and modifications to consider. © 2016, © 2016 International School Psychology Association.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-223-995-782-603 tex.type: [object Object]
Keywords: accommodations; adolescent cancer; childhood cancer; dept.csp; evidence-based practices; intervention; modifications; pediatric oncology; school psychologist